Cataloging Italian Meteorite Museum Collections Using the BN-PL National Standard: A Case Study. Issue 3 (12th July 2022) - Franza, Annarita; Faggi, Daniela; Morelli, Marco; Mancinelli, Maria Letizia; Pratesi, Giovanni
Abstract: This study sets out to investigate the usefulness of cataloging Italian meteorite museum collections using a national standard. This investigation follows a case-study design, with an in-depth analysis of the meteorite collection preserved at the Museum of Planetary Sciences in Prato, Italy, which has been recently cataloged using the BN-PL ( Beni Naturalistici–Planetologia, Naturalistic Heritage–Planetology) standard promoted by the Istituto Centrale per il Catalogo e la Documentazione (ICCD, Central Institute for Cataloging and Documentation). ICCD is a part of the Italian Ministry of Culture. The catalog cards were published in open access on the General Catalog of the Cultural Heritage (https://catalogo.beniculturali.it ).